RESEARCH ON MULTI AXIS LOW CYCLE FATIGUE LIFE PREDICTION MODELS BASED ON CRITICAL PLANE METHOD AND STRAIN PATH - LIU HongBin; CHEN Wei; WANG YanRong (Jixie qiangdu)
The article has done some research on multiaxial low cycle fatigue life evaluation methods at home and abroad,summarized multiaxial low cycle fatigue life prediction models based on Critical-Plane method and strain path and analyzed the advantages and disadvantages compared with models and applicability. It has been shown that most of the empirical prediction methods could suitable for only one or few materials so far. When they are applied on other materials,the results are usually disappointing. Meanwhile,the multi-axial fatigue failure of materials are very complicated. The current massive research work was mainly done under constant temperature and load while the studies carried out on high temperature,varying temperature and load are few. If taking notch effect,size effect,surface roughness,residual stress into account,the situation would be even more complicated. Current research on multi axis fatigue is interested in establishing life prediction model,To carry out related fatigue test,Little in-depth study of its micro mechanism The multi-axial fatigue is still a problem needing further studies.